2(3x-1)-3(4x+3)-6=5x-4(4x-1)

Simple and best practice solution for 2(3x-1)-3(4x+3)-6=5x-4(4x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x-1)-3(4x+3)-6=5x-4(4x-1) equation:


Simplifying
2(3x + -1) + -3(4x + 3) + -6 = 5x + -4(4x + -1)

Reorder the terms:
2(-1 + 3x) + -3(4x + 3) + -6 = 5x + -4(4x + -1)
(-1 * 2 + 3x * 2) + -3(4x + 3) + -6 = 5x + -4(4x + -1)
(-2 + 6x) + -3(4x + 3) + -6 = 5x + -4(4x + -1)

Reorder the terms:
-2 + 6x + -3(3 + 4x) + -6 = 5x + -4(4x + -1)
-2 + 6x + (3 * -3 + 4x * -3) + -6 = 5x + -4(4x + -1)
-2 + 6x + (-9 + -12x) + -6 = 5x + -4(4x + -1)

Reorder the terms:
-2 + -9 + -6 + 6x + -12x = 5x + -4(4x + -1)

Combine like terms: -2 + -9 = -11
-11 + -6 + 6x + -12x = 5x + -4(4x + -1)

Combine like terms: -11 + -6 = -17
-17 + 6x + -12x = 5x + -4(4x + -1)

Combine like terms: 6x + -12x = -6x
-17 + -6x = 5x + -4(4x + -1)

Reorder the terms:
-17 + -6x = 5x + -4(-1 + 4x)
-17 + -6x = 5x + (-1 * -4 + 4x * -4)
-17 + -6x = 5x + (4 + -16x)

Reorder the terms:
-17 + -6x = 4 + 5x + -16x

Combine like terms: 5x + -16x = -11x
-17 + -6x = 4 + -11x

Solving
-17 + -6x = 4 + -11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11x' to each side of the equation.
-17 + -6x + 11x = 4 + -11x + 11x

Combine like terms: -6x + 11x = 5x
-17 + 5x = 4 + -11x + 11x

Combine like terms: -11x + 11x = 0
-17 + 5x = 4 + 0
-17 + 5x = 4

Add '17' to each side of the equation.
-17 + 17 + 5x = 4 + 17

Combine like terms: -17 + 17 = 0
0 + 5x = 4 + 17
5x = 4 + 17

Combine like terms: 4 + 17 = 21
5x = 21

Divide each side by '5'.
x = 4.2

Simplifying
x = 4.2

See similar equations:

| -92+7b=13 | | 9y+3=6(y-7) | | 9/10/69 | | -6(x+4)+4x+7=7x+9 | | 47+13a=164 | | 4w-13=47 | | 25x+35y=6 | | 25x-78=72 | | 8(5s-12)-16(2s+7)=0 | | 5x-(x-3)=-21 | | d/8*-4=-6 | | 14x^2-17=0 | | 38=6(y+7)-8y | | 2x-19=73 | | 6n-27= | | 7x^2+5y=22 | | 11+n=-8 | | Z-5x=7z-9-z | | 7x+22=4x-16 | | 5x-32+y+89=180 | | 4x-16=7x+22 | | (x-3)/2-(4x-1)/6=2/3 | | https://media.edgenuity.com/evresources/3111-01-04/mc012-1.jpg | | x/15=-16 | | 1.1(.2x+1.8)+1.28=-12.14 | | x^2-53x+156=0 | | 9k^2+12k-12=0 | | 4+2(x-3)=2x-1 | | -2x+5+5x=22 | | 2y^2/32x^17 | | 4-3(x+2)=8-10 | | 0=x^2+14x-38 |

Equations solver categories